On the relationship between the multiplicities of eigenvalues in finite- and infinite-dimensional problems on graphs - Boyko, O. P.; Martinyuk, O. M.; Pivovarchik, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
It is shown that some results concerning the multiplicities of eigenvalues of the spectral problem that describes smalltransverse vibrations of a star graph of Stieltjes strings and the multiplicities of the eigenvalues of tree-patterned matricescan be used for the description of possible multiplicities of normal eigenvalues (bound states) of the Sturm – Liouvilleoperator on a star graph.